Case report: mRNA-1273 COVID-19 vaccine-associated myopericarditis: Successful treatment and re-exposure with colchicine - Valore, Luca; Junker, Till; Heilmann, Eva; Zuern, Christine S.; Streif, Matthias; Drexler, Beatrice; Arranto, Christian; Halter, Jörg P.; Berger, Christoph T. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Vaccine-induced myocarditis is a rare complication of messenger RNA (mRNA) COVID-19 vaccines. Case presentation We report a case of acute myopericarditis in a recipient of allogeneic hematopoietic cells following the first dose of the mRNA-1273 vaccine and the successful administration of a second and third dose while on prophylactic treatment with colchicine to successfully complete the vaccination. Conclusion Treatment and prevention of mRNA-vaccine-induced myopericarditis represent a clinical challenge. The use of colchicine is feasible and safe to potentially reduce the risk of this rare but severe complication and allows re-exposure to an mRNA vaccine.